SURVEI KESIAPAN DAN KEPUASAN MAHASISWA TERHADAP LAYANAN PROSES PEMBELAJARAN DALAM JARINGAN UNIVERSITAS TERBUKA SAAT PANDEMIC COVID 19 - Adhi Susilo; Ojat Darojat; Deddy Ahmad Suhardi (LPPM Universitas Terbuka, 2019)
During Covid-19 pandemic, online learning has been implemented as a strategic solution by many universities to prevent the spread of the Covid-19. This new teaching learning practice has encouraged researchers to conduct a survey of student readiness and satisfaction with the online learning services. This study aims to uncover two strategic issues including factors that influence student readiness and satisfaction and the level of student readiness and satisfaction dealing with online learning services. This research employs quantitative research methods using online surveys and involving all students who were actively registered in 2019 and 2020 both UT and non-UT students who participated in online learning services. Samples, however, were taken from all respondents covering western, central, and eastern Indonesia. It was discovered that structurally, supporting aspects contribute around 37%, prospect aspects 25%, benefit aspects 23%, and constraint aspects 11%, towards a dimension of the formation of participants' online learning perceptions. The findings show that participants have quite different views on supporting aspects, benefits, or prospects of online learning from the aspects of constraints. The relationship among the three distribution groups of variable categories shows three quite different positions in terms of participants' perceptions on online learning, namely accepting, moderate or opposing positions. Their opinion on online learning programs, during the Covid-19 outbreak, participants differed in their opposing positions on the one hand and moderate positions on the other, especially regarding costs, trends, and prices of devices/supporting equipment for online learning participants.